Remedy for victim: Discourse on the roles and norms of corruption claim in transnasional investment arbitration proceeding - Lakso Anindito (Komisi Pemberantasan Korupsi, 2024)
Although various international forums, including in The Conference of the States Parties (COSP) United Nations Convention Against Corruption (UNCAC) in 2016, have advocated for initiatives to address transnational corruption, remedies for its victims remain an unaddressed gap in the enforcement of foreign bribery offenses. In this scenario, World Duty-Free Company Limited v. Republic of Kenya demonstrates an alternative strategy to nullify the investment protection agreement. This is due to instances where the investment process is tainted by bribery, thereby protecting the victim country from unfair business practices and encouraging private actors to comply with ethical standards when conducting business activities. However, the norms used to justify the decision pose a significant obstacle, as corruption regulation varies across different investment treaties. These norms directly influence how corruption issues are addressed in arbitration proceedings. This paper will elaborate on the roles of arbitration as an alternative remedy for transnational corruption in victim countries and examine the potential norms that available to arbitrators from the perspective of societal constitutionalism theory.